2017
DOI: 10.1016/j.joca.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation profiling of articular cartilage reveals significant epigenetic alterations in Kashin-Beck disease and osteoarthritis

Abstract: Our data implicate epigenetic dysregulation of a host of genes in KBD and OA. Furthermore, we observed common causal epigenetic changes shared by KBD and OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…In line with chondrosarcomas, accumulating evidence also shows epigenetic dysregulation in OA [ 180 , 181 ]. However, IDH mutations have not been detected in AC so far, but inflammatory cytokines suppressed IDH and TET activity in human primary chondrocytes in vitro [ 182 ], a mechanism which might also apply in chondrosarcomas without IDH mutation.…”
Section: Chondrosarcoma Treatmentmentioning
confidence: 97%
“…In line with chondrosarcomas, accumulating evidence also shows epigenetic dysregulation in OA [ 180 , 181 ]. However, IDH mutations have not been detected in AC so far, but inflammatory cytokines suppressed IDH and TET activity in human primary chondrocytes in vitro [ 182 ], a mechanism which might also apply in chondrosarcomas without IDH mutation.…”
Section: Chondrosarcoma Treatmentmentioning
confidence: 97%
“…They identified 45 genes with significant DNA methylation differences, including three genes which were hypomethylated in both OA and RA patients 14 . The second, by Wang and colleagues, was a small study which included five OA, five normal (neck of femur fracture), and five Kashin-Beck disease (KBD), an endemic osteochondropathy associated with accelerated OA in Siberia, Korea, and China 15 . They identified several differentially methylated positions (DMPs) by Illumina 450 k array associated with both KBD and OA, including 367 which overlapped (were associated with both OA and KBD), corresponding to 182 genes, all with matching methylation directions in both OA and KBD (i.e., hypermethylated or hypomethylated in both compared to control).…”
Section: Epigenetics: Dna Methylationmentioning
confidence: 99%
“…Some studies suggested that some genes might contribute to the development of KBD, such as GPX1 , [10] GPX4 , [11] SELS , [9] SEPP , [12] ADAM12 , [13] Col2A1 , [14] Bcl-2 , Bax , and Fas . [15] But these studies only provided a limited explanation for the KBD occurrence and insufficiently revealed their roles and functions in the development of KBD. In the whole genome-wide, these genes do not play independent roles; instead, these genes form biological function and pathway networks through their intricate interactions, which can give us a more complete picture of their genetic function contributing to the development of KBD.…”
Section: Introductionmentioning
confidence: 99%